Penentuan Jumlah Operator Untuk Mengurangi Keterlambatan pada Proses Pengemasan Menggunakan Simulasi ProModel - Mirna Lusiani; Kenrick Filbert (JIEMS (Journal of Industrial Engineering and Management Systems), 2019)
In the current era of modernization, the development of the cosmetic industry in the world is developing very rapidly. One of the cosmetics that is the main requirement for women is lipstick. PT. Cedefindo is one of the cosmetic manufacturers that produce SASC lipstick. During 2017, there were problems in the lipstick packaging process. Based on the results of identification, the delay is caused by the buildup during the weighing process so that the next process becomes slow and sometimes makes the operator idle. The consequence that arises is often not achieving daily production targets. Therefore, this research aims to reduce the delay in the lipstick packaging process, especially the lipstick packaging section. In evaluating and analyzing the lipstick packaging system, research uses system simulation with the help of ProModel software. The result shows that adding would reduce the delay in the lipstick packaging process. Minimizing the production costs related to the packaging process is conducted by reducing operator unused work shifts. Therefore, adding some operators can reduce production costs especially on operator salaries up to 75%. The feasible solution is to assign 3 operators on low demand rate, 4 operators at normal demand rate and high demand rate.